2018
DOI: 10.17235/reed.2018.5324/2017
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of follow-up of the Spanish cohort of the European PreventCD study: the lessons learned

Abstract: Aim: to evaluate the influence of gluten consumption on celiac disease development and to describe its natural history in the Spanish cohort of the European PreventCD study.Methods: prospective multi-center double blind study of 225 children that were followed up from birth. All cases were HLA-DQ2/HLA-DQ8 positive with a 1 st degree relative with celiac disease and were followed up in three centers from Madrid, Reus and Valencia. Gluten intake was determined between four and ten months according to the protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…However, infant gluten interventions beyond this tight time window with longer intervals have not been fully evaluated. However, recent publications with longer follow-up in the PREVENT-CD cohort show contradictory results (37)(38)(39). A study based on the Italian study population found that children who developed celiac disease by the age of 6 years had significantly higher gluten consumption after 24 months of age compared with children who did not develop celiac disease (39).…”
Section: Discussionmentioning
confidence: 99%
“…However, infant gluten interventions beyond this tight time window with longer intervals have not been fully evaluated. However, recent publications with longer follow-up in the PREVENT-CD cohort show contradictory results (37)(38)(39). A study based on the Italian study population found that children who developed celiac disease by the age of 6 years had significantly higher gluten consumption after 24 months of age compared with children who did not develop celiac disease (39).…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies have noted an association between higher gluten intake and CDA/CD—both at first introduction 13 and cumulatively throughout childhood, 14–16 consistent with patterns during the Swedish CD epidemic. However, when the entire PreventCD cohort was considered, this association held for only the DQ2.2/DQ7 17 heterozygotes, and extended follow‐up of the Spanish cohort showed no effect of the amount of gluten consumption in the first 3 years on the development of CD through age 6 18 . More rigorous randomised controlled trials (RCTs) failed to show an effect of timing of gluten introduction 19 or breastfeeding, 20 nor have meta‐analyses including various study designs identified an effect 21 …”
Section: Risk Factors and Preventionmentioning
confidence: 94%
“…However, in this multicenter study, which included several European countries, they did find differences for the HLA-DQ2.2/-DQ7 risk group, observing that a gradual increase in the amount of gluten between 11 and 18 months can act as a modulating factor for this specific group. Later, the data from this cohort in Spain were analyzed [91], concluding that the consumption of gluten during the first 3 years of life does not influence the risk of developing CD before 6 years of age.…”
Section: Early Gluten Consumption and Development Of Celiac Diseasementioning
confidence: 99%